Protective effect of epimedium combined with oligomeric proanthocyanidins on exercise-induced renal ischemia-reperfusion injury of rats - Zhang, Hua (Int J Clin Exp Med, 2014)
Objective: This paper studied the protective effect and mechanism of epimedium combined with oligomeric proanthocyanidins on exercise-induced renal ischemia-reperfusion injury of rats. Methods: In the experiment, the rats were given exhaustive swimming training and then their blood urea nitrogen (BUN) and other biochemical indexes were measured after they were given gastric perfusion with 6.01 g/kg doze of epimedium and 50 mg/kg doze of oligomeric proanthocyanidins for 56 days. Results: The result indicated that 8 weeks of over training led to ischemia-reperfusion injury of rats. Moreover, their kidney tissues were significantly changed pathologically and renal functions drastically damaged. BUN and serum creatinine increased and EOM group (P < 0.05), OPCOM group (P < 0.05) and EOPCOM group (P < 0.01) were lower than OM group. EOPCOM group was lower than OPCOM group. SOD activity decreased, EOM group (P < 0.05), OPCOM group (P < 0.05), EOPCOM group (P < 0.01) higher than OM group, and EOPCOM group (P < 0.05) higher than OPCOM group. The content of MDA increased, EOM group (P < 0.05), OPCOM group (P < 0.05), EOPCOM group (P < 0.01) lower than OM group, and EOPCOM group (P < 0.05) lower than OPCOM group. Conclusion: Both epimedium and oligomeric proanthocyanidins can boost SOD activity, clean oxygen radicals, clean and alleviate peroxidation of lipids, which exert protection on exercise-induced renal ischemia-reperfusion. The two combined yield a much better result.